Exploring the source of TYLCV resistance in Nicotiana benthamiana - Hayashi, Satomi; Souvan, Jacqueline M.; Bally, Julia; de Felippes, Felipe F.; Waterhouse, Peter M. (Frontiers in Plant Science, 2024)
Tomato Yellow Leaf Curl Virus (TYLCV) is one of the most devastating pathogens of tomato, worldwide. It is vectored by the globally prevalent whitefly, Bemisia tabaci, and is asymptomatic in a wide range of plant species that act as a virus reservoir. The most successful crop protection for tomato in the field has been from resistance genes, of which five loci have been introgressed from wild relatives. Of these, the Ty-1/Ty-3 locus, which encodes an RNA-dependent RNA polymerase 3 (RDR3), has been the most effective. Nevertheless, several TYLCV strains that break this resistance are beginning to emerge, increasing the need for new sources of resistance. Here we show the differential response of two isolates of Nicotiana benthamiana to TYLCV infection. Our study indicates the presence of a novel, but yet to be identified, TYLCV resistance gene in a wild accession of N. benthamiana.